Strengthening Students’ Noble Character Through School–Parent Collaboration: Memperkuat Karakter Mulia Siswa Melalui Kerjasama Sekolah dan Orang Tua - Nadhifah, Fany Rizki; Kurniawan, Machful Indra (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Character education in primary schools requires not only moral instruction but also consistent habituation supported by school and family. Specific Background: SDI Al-Chusnaini integrates religious routines, extracurricular programs, and communication tools to strengthen students’ noble character. Gap: Limited studies have examined how these strategies operate simultaneously in an Islamic full-day school context. Aim: This study explores the strategies used to strengthen and form students’ noble character through collaboration between teachers and parents. Methods: A descriptive qualitative design was employed with data collected through observation, interviews, and documentation, analyzed using source triangulation. Results: Findings show that character strengthening occurs through religious habituation, structured extracurricular activities, and the consistent use of a communication book that aligns guidance at school and home. Novelty: This study highlights the integrated use of religious programs and communication systems as a continuous monitoring mechanism. Implications: Schools can enhance character formation by ensuring strong teacher–parent collaboration and routine-based programs that support honesty, responsibility, and religiosity. Highlights• Character building through religious and extracurricular programs• Consistent school–parent collaboration via communication books• Strengthening honesty, responsibility, and religiosity in daily practice Keywords: Character Education, Collaboration, Primary School, Habituation, Religious Programs